2002
DOI: 10.4141/p01-122
|View full text |Cite
|
Sign up to set email alerts
|

Leaf and stem dry matter digestibility and ruminal undegradable proteins of alfalfa cultivars

Abstract: R. 2002. Leaf and stem dry matter digestibility and ruminal undegradable proteins of alfalfa cultivars. Can. J. Plant Sci. 82: 383-393. Increased dry matter digestibility and ruminal undegradable protein (RUP) concentration are traits highly ranked to improve the nutritive value of forage legumes. Whole-plant, leaf, and stem samples of 27 alfalfa cultivars grown in eastern Canada were analysed for total nitrogen (TN), in vitro RUP, and in vitro dry matter digestibility (IVDMD). The objectives were to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
0
24
1
2
Order By: Relevance
“…The significant difference (P<0.05) among the tested genotypes was in agreement with (Diriba et al, 2014) and in disparity with others finding (Mekuanint et al, 2015). Volenec and Cherney (1990) reported significant differences in IVDMD among alfalfa cultivars and these differences were indicated to be associated with variation in digestibility of the stem fraction (Tremblay et al, 2002). A significant difference among 14 alfalfa varieties was also reported for IVDMD, with values ranging from 59 to 66% (Kamalak et al, 2005), which indeed were much lower than those recorded in the present work.…”
Section: Herbage Nutritive Value At Forage Harvesting Stagecontrasting
confidence: 55%
“…The significant difference (P<0.05) among the tested genotypes was in agreement with (Diriba et al, 2014) and in disparity with others finding (Mekuanint et al, 2015). Volenec and Cherney (1990) reported significant differences in IVDMD among alfalfa cultivars and these differences were indicated to be associated with variation in digestibility of the stem fraction (Tremblay et al, 2002). A significant difference among 14 alfalfa varieties was also reported for IVDMD, with values ranging from 59 to 66% (Kamalak et al, 2005), which indeed were much lower than those recorded in the present work.…”
Section: Herbage Nutritive Value At Forage Harvesting Stagecontrasting
confidence: 55%
“…Bélanger and McQueen (1998) reported that the proportion of leaves in timothy was higher in summer regrowth (LWR = 0.5) than in spring growth (LWR = 0.3). In alfalfa, Tremblay et al (2002) reported that the LWR of 27 cultivars seeded in three replicates during 2 yr and harvested during the 2 subsequent production years was lower in spring growth (0.39) than in summer regrowth (0.45). Onstad and Fick (1983) also reported a lower LWR in spring than in regrowth of alfalfa at the same physiological age.…”
Section: Growth Period and Species (Experiments 3)mentioning
confidence: 99%
“…Numerous studies (Jung and Allen 1995;Ayres et al 1998;Elizalde et al 1999;Ferdinandez and Coulman 2001;Lyon et al 2001) have shown that yield and nutritional values of forages are affected by growth stage, forage species, cultivar (Kunelius 1990;Griffin et al 1994;Lundvall et al 1994;Tremblay et al 2000Tremblay et al , 2002Tremblay et al , 2003, soil type (Aumont and Salas 1996), climate conditions (e.g., rainfall, temperature) (Minson and McLeod 1970;Mathison et al 1996) and growing conditions (Cox et al 1994). In Canada, Kunelius (1990) reported dry matter production, fiber composition, and plant characteristics of cool-season grasses including timothy under two harvest systems.…”
mentioning
confidence: 99%
“…Bélanger and McQueen (1996) reported the differences in digestibility and cell wall concentration of early-and late-maturing timothy (Phleym pratense L.) cultivars. Tremblay et al (2000Tremblay et al ( , 2002Tremblay et al ( , 2003 reported significant effects of alfalfa cultivars on in vitro ruminal undegradable proteins (Tremblay et al 2000), leaf and stem dry matter digestibility and ruminal undegradable proteins (Tremblay et al 2002) and protein fractions (Tremblay et al 2003). Information, however, is lacking on rumen degradation characteristics of different cultivars of alfalfa and timothy grown under the climate conditions of western Canada.…”
mentioning
confidence: 99%